Peaceful selves : personhood, nationhood, and the post-conflict moment in Rwanda - Eramian, Laura (Berghahn Books, 2018)
"This in-depth ethnographic study of personhood in post-genocide Rwanda, carried out over a decade, investigates how Rwandans grapple with what kinds of persons they ought to become in the wake of the violence. While Rwandans strive to be agents of change in a new era of modern nationhood, they are also devastated by the genocide and struggle to recover a sense of selfhood and belonging in the absence of kin, friends, and neighbors. The author explores the effect of this situation on ordinary lives, caught in global post-conflict imperatives to remember and to forget, to mourn and to prosper."--Back cover